Actuator Fault Tolerant LQG Control of a Water Delivery Canal - Lemos, João (2013)
The problem of reconfiguration of the control system to mitigate the effects of actuator faults in a water delivery canal is addressed in this paper. When a fault in an actuator is detected and isolated, the controller is reconfigured by changing the set of manipulated and process variables and using a different controller, associated to a different plant model, in a hybrid systems framework. In order to prevent instability that may be associated with switching among controllers, a dwell time condition is used. Both centralized and distributed control, a game approach is followed to coordinate the different local controllers. Experimental results are presented.